2019
DOI: 10.3389/fimmu.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on Immunoregulation of Macrophages by Plant Polysaccharides

Abstract: Polysaccharides are among the most important members of the biopolymer family. They are natural macromolecules composed of monosaccharides. To date, more than 300 kinds of natural polysaccharide compounds have been identified. They are present in plants, animals, and microorganisms, and they engage in a variety of physiological functions. In the 1950s, due to the discovery of their immunoregulatory and anti-tumor activities, polysaccharides became a popular topic of research in pharmacology, especially in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
183
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(192 citation statements)
references
References 88 publications
3
183
1
5
Order By: Relevance
“…The plant polysaccharides are derived from plant roots, leaves, skins, seeds, and flowers. It is well known that the plant polysaccharides from Chinese herb own a wide variety of biological activities, such as antioxidant, antiinflammatory, antiviral, antitumor, hypoglycemic, and immunity-stimulating properties ( Li et al., 2015 ; Xie et al., 2016 ; Chen and Huang, 2018 ; Yin et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant polysaccharides are derived from plant roots, leaves, skins, seeds, and flowers. It is well known that the plant polysaccharides from Chinese herb own a wide variety of biological activities, such as antioxidant, antiinflammatory, antiviral, antitumor, hypoglycemic, and immunity-stimulating properties ( Li et al., 2015 ; Xie et al., 2016 ; Chen and Huang, 2018 ; Yin et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological and clinical studies have shown that ABP can exert antioxidant, antiallergic, immunomodulatory, arthritis alleviation, antiinflammatory, hepatoprotective, and anticancer effects ( Kim and Park, 2010 ; Bang et al., 2012 ; Jang et al., 2012 ). Previous studies have indicated that ABP have significant immune-stimulating activity, which are achieved through the generation of reactive oxygen species, the secretion of cytokines, cell proliferation, and the phagocytic activity of macrophages ( Li and Li, 1997 ; Yin et al., 2019 ; Zhang et al., 2019 ). Hence, it has the potential to be used as an immune modulator in animal nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…TLR4 is a very important class of membrane receptors that are expressed on the surfaces of macrophages and mediate the activation of macrophages by converting extracellular signals. Binding of ligands such as polysaccharides to TLR4 leads to a change in the complex between the cytoplasmic region of TLR and the adaptor protein MyD88 [23]. The data presented in this paper suggest that TLR4 molecule is responsible for the EPSAH-induced macrophage activation for NO secretion by stimulating the TLR4-mediated signaling pathway.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies have shown that the botanical polysaccharides can enhance and/or activate macrophage immune responses [23]. Macrophage is the most important professional phagocyte and is able to clear large amounts of various materials.…”
Section: Discussionmentioning
confidence: 99%
“…Многочисленные исследования показали, что растительные полисахариды регулируют иммунную систему несколькими способами и на разных уровнях. Они не только активируют иммунные клетки, в том числе Т-клетки, В-лимфоциты, макрофаги и естественные клетки-киллеры, но также активируют комплементы и стимулируют выработку цитокинов [28].…”
Section: Introductionunclassified